SHARIA CONFORMITY, PROFITABILITY AND PROFIT DISTRIBUTION AT BANK SYARIAH INDONESIA - Fernando Africano; Isnurhadi; Yuliani; Mu’izzuddin (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Islamic banks are expected to achieve financial sustainability while maintaining compliance with Sharia principles. Therefore, evaluating Islamic banking performance requires an integrated approach that considers both financial and Sharia dimensions. This study aims to evaluate the performance of Bank Syariah Indonesia (BSI) using the Sharia Conformity and Profitability (SCnP) model and analyze its implications for profit distribution during 2021–2025. A quantitative descriptive approach was employed using secondary data obtained from BSI Annual Reports. The analysis calculated the Islamic Income Ratio (IIR), Islamic Investment Ratio (IInvR), Profit Sharing Ratio (PSR), and Return on Assets (ROA), which were integrated into the SCnP framework. The findings indicate consistent growth in total assets, net profit, and profit distribution throughout the observation period. The Islamic Income Ratio remained above 80%, while the Profit Sharing Ratio increased from 36.13% in 2021 to 45.29% in 2025, indicating stronger implementation of Sharia-based financing. The SCnP results demonstrate that BSI maintained high Sharia conformity and profitability, reflecting balanced financial performance and compliance with Islamic principles. These findings suggest that stronger profitability and Sharia conformity support sustainable profit distribution. This study highlights the usefulness of the SCnP model for comprehensively evaluating Islamic banking performance and supporting sustainable Sharia-compliant banking practices.